2020
DOI: 10.1016/j.compag.2020.105221
|View full text |Cite
|
Sign up to set email alerts
|

Hyperspectral remote sensing for assessment of chlorophyll sufficiency levels in mature oil palm (Elaeis guineensis) based on frond numbers: Analysis of decision tree and random forest

Abstract: A common practice of chlorophyll (chl) determination has been using the chemical analysis that is destructive and time-consuming. A current prospective alternative method such hyperspectral remote sensing offers a non-destructive measurement of chl which provides a result in the rapid and real-time manner. Therefore, the ultimate aims of this study were to propose the chls (chl a, chl b, total chl content (TCC) and relative chl content (RCC)) sufficiency levels via Jenks Natural Breaks (JNB) classification and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(27 citation statements)
references
References 42 publications
0
27
0
Order By: Relevance
“…This clearly proved the merit of the RF classifier in modeling high-dimensional data because it intrinsically works with a random subset of features instead of all of the features of the model at each splitting point of an individual tree in the forest, thereby averaging away the feature variance. Numerous pathological and entomological vegetation studies have reported that SVM succeeded in modeling f VIs extracted from spectral bands [ 39 , 89 , 90 ], while at the same time the modeling performance of for the RF classifier was found to be stable and superlative with transformed spectral reflectance data [ 91 , 92 , 93 ].…”
Section: Discussionmentioning
confidence: 99%
“…This clearly proved the merit of the RF classifier in modeling high-dimensional data because it intrinsically works with a random subset of features instead of all of the features of the model at each splitting point of an individual tree in the forest, thereby averaging away the feature variance. Numerous pathological and entomological vegetation studies have reported that SVM succeeded in modeling f VIs extracted from spectral bands [ 39 , 89 , 90 ], while at the same time the modeling performance of for the RF classifier was found to be stable and superlative with transformed spectral reflectance data [ 91 , 92 , 93 ].…”
Section: Discussionmentioning
confidence: 99%
“…This type of classification uses the Jenks optimization algorithm to classify attributes. It seeks to minimize the average deviation from the mean for each class while maximizing the deviation from the means of other classes-that is, to reduce the variance within classes and maximize the variance among classes [73,74].…”
Section: Data Analysis and Resultsmentioning
confidence: 99%
“…The observed family is a valuable source of new palm trees with higher oil yields and improved bunch characteristics. The work in [42] proposed Jenks natural breaks (JNB) for the classification of chlorophyll sufficiency levels and relative chlorophyll content. The best subset of frond number, chlorophyll-sensitive wavelengths, and the classifier to categorize the chlorophylls according to the nominated sufficiency levels were suggested using a hyperspectral remote sensing platform.…”
Section: Multipurpose Classificationmentioning
confidence: 99%